Pembangunan Biogas Untuk Mengolah Kotoran Sapi Di Kampung Pujo Kerto - Imam Santosa; Daria Br. Ginting; Enro Sujito; Arie Nugroho; Titi Astuti (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The development priorities in Pujo Kerto village in 2023 are improving village roads, increasing agricultural activities and environmental sanitation, especially the use of cow dung waste. Currently in Pujo Kerto Village, the community has not utilized cow dung waste properly. The situation analysis above is the basis for Biodigester development activities in Pujo Kerto Village. The aim of the community service activities for the Tanjungkarang Ministry of Health's PPDM Health Polytechnic scheme in Pujo Kerto Village: Guiding the Pujo Kerto Village community in constructing Biogas buildings, monitoring biogas construction and the use of biogas for cooking, as well as liquid fertilizer used for watering plants. The methodology for community service activities is as follows: Preparation, Implementation and Evaluation. The results of the activities are as follows: 1) Construction of 1 unit of Cow Dung Biogas building 2) Availability of biogas fuel for cooking for 1 household 3) Availability of Liquid Fertilizer for watering plants.